Conductance Response of Tin Nanowires to the External Axial Pressure Load - Gao, F; Li, H; Zhang, X. Q; Li, Y. F; Liew, K. M (Journal of physical chemistry. C, 2010)
Five different optimized Sn nanowires embedded in single-walled carbon nanotubes (SWCNTs) are obtained by means of molecular dynamics (MD) simulation. Growth of Sn nanowires follows a helical or parallel pattern in confined space. Optimized Sn nanowires subject to compression are investigated. Results reveal that a four-strand-parallel nanowire can resist the highest pressure load among these five kinds of nanowires studied. The growth pattern of a nanowire determines its conductance response to the pressure load. Interestingly, conductance of double-helical and four-strand-parallel nanowires (which have an even number of atomic chains) increases with pressure load, while the conductance of three-strand-helical and five-strand-helical nanowires (which have an odd number of atomic chains) is found to decrease with pressure load. On the basis of the conductance response of the nanowire to the external pressure load, nanosensors can be fabricated to detect the stress and strain of nanostructured materials.